Improving Quality of Water from Murchison Bay using Clay from Chelel, Kapchorwa District, Ugandao (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
Pollution resulting from increased human activities is threatening Lake Victoria, its effects are characterized by eutrophication, high turbidity, pH, iron(II) concentration and chemical oxygen demand (COD). In this study we have investigated the effect of Fe-montmorillonite clay from Chelel on turbidity, pH, concentration of iron, total suspended soils, total nutrients and COD of water sampled from Murchison bay watershed of Nakivubo channel south of Kampala. Varying amounts of clay powder was vigorously stirred with water samples for 5 minutes, filtered using Whitman paper at ambient temperatures. The optimum concentration of clay of 0.4gl-1 was found to produce 73.5+ 2% fall in COD indicating elimination of microbes and organic waste. The pH of water became 6.3+ 0.2 showing that impurities had been bound to clay. The turbidity of filtrate dropped to 15.7+ 0.3NTUshowing that clarity of water was improved by adsorption of suspended solids to clay minerals. The concentration of iron(II) fell from 3.7 + 0.3 to 2.5+ 0.2mgl-1 indicating fairly high extent of heavy metal removal from Murchison bay (MB) waters. The TSS and nutrients in MB water   also decreased greatly when clay was stirred with water at ambient temperatures. The available data can be relied on to recommend use of this clay in treatment of waste water and/or sewage from Kampala. Further studies on combined use of clays with alums, zeolites and/or lime need to be carried out.